2021
DOI: 10.1007/s10461-021-03526-z
|View full text |Cite
|
Sign up to set email alerts
|

Awareness of, Willingness to Take PrEP and Its Actual Use Among Belgian MSM at High Risk of HIV Infection: Secondary Analysis of the Belgian European MSM Internet Survey

Abstract: We examined PrEP awareness, willingness to take it and early PrEP use among men who have sex with men (MSM) at increased risk of HIV acquisition in Belgium. This analysis of the Belgian EMIS data of 2017-2018 adopts a cascade approach, with the following steps quantified as conditional probabilities: being eligible for, aware of, and willing to take PrEP and PrEP use. One out of three MSM was eligible to use PrEP according to the operationalized Belgian reimbursement criteria. PrEP awareness was lower among so… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 51 publications
(60 reference statements)
2
4
0
Order By: Relevance
“…Based on the EMIS-2017 data, we estimated that 34.6% (32.87–36.45; 95% CI) of the Belgian MSM population would be eligible to receive Pre-Exposure Prophylaxis (PrEP). This estimate is similar to estimates from previously published studies from Belgium and Europe [ 62 , 64 , 65 ]. According to the other two definitions of high-activity MSM, 30.41% (28.69–32.19; 95% CI) and 27.90% (26.23–29.64; 95% CI) of the EMIS-2017 participants reported more than 15 total and casual partners over a 12-month period, respectively.…”
Section: Methodssupporting
confidence: 91%
“…Based on the EMIS-2017 data, we estimated that 34.6% (32.87–36.45; 95% CI) of the Belgian MSM population would be eligible to receive Pre-Exposure Prophylaxis (PrEP). This estimate is similar to estimates from previously published studies from Belgium and Europe [ 62 , 64 , 65 ]. According to the other two definitions of high-activity MSM, 30.41% (28.69–32.19; 95% CI) and 27.90% (26.23–29.64; 95% CI) of the EMIS-2017 participants reported more than 15 total and casual partners over a 12-month period, respectively.…”
Section: Methodssupporting
confidence: 91%
“…Notably, almost all (96%) PrEP starters in 2020 fell under the classification of ‘men who have sex with men’ (MSM), while about half of all new diagnoses in Belgium are attributed to heterosexual sex ( 21 ). Surveys conducted in 2014 and 2017, respectively among people with a sub-Saharan African migrant background and MSM living in Belgium, also found that about one third of both populations (30.3 and 33.2%, respectively) was eligible for PrEP according to Belgian eligibility criteria (see Supplementary Material 1 ) ( 24 , 25 ). Wary of their limited generalizability, these data suggest a remaining unmet need for PrEP in Belgium.…”
Section: Introductionmentioning
confidence: 96%
“…The proportion of participants aged ≥40 years in class 1 was 7.6% higher than that of class 2 and the proportion having a monthly income of ≤US $713 in class 1 was 7.5% higher than that of class 2. Older MSM may have a poorer economic status and were less likely to be aware, or have an inappropriate understanding of, PrEP than MSM ≤30 years old, which made them less likely to use it [41,42]. Improving HIV prevention may involve providing counseling on PEP and PrEP use during HIV testing for high-risk targets, including basic knowledge, side effect management, using reminders to ensure compliance, and providing financial and social support that increases the likelihood of preventive medication use [43].…”
Section: Principal Resultsmentioning
confidence: 99%